2001
DOI: 10.1590/s1517-83822001000100011
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of herpotrichiellacious fungi from the environment

Abstract: Herpotrichiellaceous fungi, common agents of chromoblastomycosis and phaeohyphomycosis, were searched in samples of rotten wood, leaf littler, bark and soil of the rhizosphere, collected in the Centro Nacional de Pesquisas de Florestas/EMBRAPA, Colombo, PR, Brazil. Morphological analyses of macro, optic and scanning electron microscopy, as well as the determination of the nutritional pattern of the isolated strains were carried out for a taxonomical study. In a total of 17 colonies, 3 isolates (17.6%) were ide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
25
0
1

Year Published

2004
2004
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 15 publications
(26 reference statements)
1
25
0
1
Order By: Relevance
“…In nature, monoaromates are found in trace amounts in plant debris, thorns, and wood cortex, which provide microhabitats for these fungi (74). There is a strong correlation between the traumatic implantation of potential natural sources of infection and CBM lesions (74)(75)(76)(77)(78)(79)(80). This route of infection may be supported by clinical reports of patients exhibiting the presence of fragments of plant material at the site where they experienced a previous trauma.…”
Section: Epidemiology Potential Environmental Sources Of Infectionmentioning
confidence: 92%
See 3 more Smart Citations
“…In nature, monoaromates are found in trace amounts in plant debris, thorns, and wood cortex, which provide microhabitats for these fungi (74). There is a strong correlation between the traumatic implantation of potential natural sources of infection and CBM lesions (74)(75)(76)(77)(78)(79)(80). This route of infection may be supported by clinical reports of patients exhibiting the presence of fragments of plant material at the site where they experienced a previous trauma.…”
Section: Epidemiology Potential Environmental Sources Of Infectionmentioning
confidence: 92%
“…Ruben et al and Fernández-Zeppenfeldt et al reported the identification of Cladophialophora in cactus plants (83,89), but de Hoog et al showed that this was a molecular sibling, C. yegresii (33). Vicente et al reported the identification of mainly saprobic Fonsecaea species such as F. minima and F. erecta in plant thorns close to the habitat of patients with CBM due to F. pedrosoi, while pathogenic strains were recovered only exceptionally (56,74,76). In 1937, Conant thought that Cadophora americana recovered from wood pulp was identical to Phialophora verrucosa, which potentially caused CBM (90), but recently, Feng et al proved that the P. verrucosa complex contains clinical species next to environmental species (91).…”
Section: Epidemiology Potential Environmental Sources Of Infectionmentioning
confidence: 99%
See 2 more Smart Citations
“…Dematiaceous fungi are saprobes found mainly in soils and organic matter functioning as decomposition agents (15). A natural characteristic of these microorganisms is their dark cellular pigment, which is the result of a melanization process.…”
Section: Introductionmentioning
confidence: 99%